2002
DOI: 10.1093/nar/30.4.921
|View full text |Cite
|
Sign up to set email alerts
|

RNomics in Archaea reveals a further link between splicing of archaeal introns and rRNA processing

Abstract: The bulge-helix-bulge (BHB) motif recognised by the archaeal splicing endonuclease is also found in the long processing stems of archaeal rRNA precursors in which it is cleaved to generate pre-16S and pre-23S rRNAs. We show that in two species, Archaeoglobus fulgidus and Sulfolobus solfataricus, representatives from the two major archaeal kingdoms Euryarchaeota and Crenarchaeota, respectively, the pre-rRNA spacers cleaved at the BHB motifs surrounding pre-16S and pre-23S rRNAs subsequently become ligated. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
109
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 39 publications
13
109
0
Order By: Relevance
“…RNA-seq methodology revealed an abundant genome-wide presence of circRNAs in the transcriptome of the archaeon Sulfolobus solfataricus 10 such as tRNA introns and rRNA processing intermediates, as well as several protein-coding genes, and many smaller non-coding RNAs (e.g., box C/D RNAs). This genome-wide study is also in agreement with earlier studies that have revealed the presence of circular forms in excised tRNA-introns, 11,12 introns of rRNAs, 13,14 rRNAs processing intermediates 15 and box C/D RNAs in archaea. 16 Note that box C/D RNAs guide site-specific modification (2 0 -0-methylation) of rRNA and small nuclear RNA in eukaryotes and tRNA in archaea.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…RNA-seq methodology revealed an abundant genome-wide presence of circRNAs in the transcriptome of the archaeon Sulfolobus solfataricus 10 such as tRNA introns and rRNA processing intermediates, as well as several protein-coding genes, and many smaller non-coding RNAs (e.g., box C/D RNAs). This genome-wide study is also in agreement with earlier studies that have revealed the presence of circular forms in excised tRNA-introns, 11,12 introns of rRNAs, 13,14 rRNAs processing intermediates 15 and box C/D RNAs in archaea. 16 Note that box C/D RNAs guide site-specific modification (2 0 -0-methylation) of rRNA and small nuclear RNA in eukaryotes and tRNA in archaea.…”
Section: Introductionsupporting
confidence: 92%
“…Formation of the circular 5S rRNA could be compatible with the proposed processing mechanism of the archaeal pre-5S-RNA possibly 31 but it is unclear whether this potential circular form corresponds to an additional processing intermediate or the mature 5S rRNA. 15 When linear isoforms of the naturally occurring C/ D box and 5 S rRNAs were used in binding (Fig. 3A) and circularization ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This step is followed by the joining of the tRNA exons catalyzed by a tRNA splicing-specific ligase in Eukarya; however, little is known about the tRNA ligation mechanism in Archaea (3). The archaeal splicing endonuclease recognizes a consensus bulgehelix-bulge (BHB) structure that is found at the intron-exon junctions of intron-containing tRNA (4), rRNA (5,6), and mRNA (7). The BHB motif exhibits pseudo-twofold symmetry with the two 3-nt bulges present on the same minor groove face of the central 4-bp helix, termed the 3-4-3 BHB (8).…”
mentioning
confidence: 99%
“…45 Northern blot analysis of CRISPR pre-RNA revealed the presence of antisense transcripts for each of the S. acidocaldarius CRISPR loci. 55 Bi-directional transcription was also experimentally verified in S. solfataricus CRISPR loci 26,55,67,68 and was confirmed by analyzing publicly available transcriptome data. 69 However, the loci were primarily transcribed from the leader strand.…”
Section: Crispr Transcription and Regulation In Sulfolobalesmentioning
confidence: 68%